2014
DOI: 10.21106/ijma.34
|View full text |Cite
|
Sign up to set email alerts
|

Social and Economic Barriers to Exclusive Breastfeeding in Rural Zimbabwe

Abstract: Objectives:Exclusive breast feeding (EBF) uptake in Zimbabwe is very low. Given that EBF is a physiological process which transpires in a specific socio-economic milieu, this study investigates the socio-economic factors militating against its uptake.Methods:The study used a mixed research methodology. The concurrent nested model of mixed methods was utilized using one data collection phase, during which both quantitative and qualitative data were collected simultaneously.Results:The research noted that factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 4 publications
(11 reference statements)
3
19
0
4
Order By: Relevance
“…Mammary gland is a complex gland that originates during the embryonic stage and develops quickly from the pubertal stage with ductal growth and early alveolar development during menstrual cycles; mammary tissue then undergoes proliferation, differentiation and death during pregnancy, lactation and involution stages, respectively [ 2 ]. The main function of the mammary gland is to secret milk for infant nutrition [ 3 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammary gland is a complex gland that originates during the embryonic stage and develops quickly from the pubertal stage with ductal growth and early alveolar development during menstrual cycles; mammary tissue then undergoes proliferation, differentiation and death during pregnancy, lactation and involution stages, respectively [ 2 ]. The main function of the mammary gland is to secret milk for infant nutrition [ 3 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Milk production is an evolutionary necessity and this process is tightly regulated at a local level, i.e. within the mammary gland itself, by hormones and other factors [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, similar studies conducted in Colombia and other countries have explored multiple socioeconomic variables (e.g., work, government policies) that were not considered in this study (Abou-ElWafa & El-Gilany, 2019;Benjumea et al, 2011;Cabrera et al, 2004;Caleyachetty et al, 2013;Mateus, 2012;Muchacha & Mtetwa, 2014;Rodríguez-García & Acosta-Ramírez, 2008). Thus, future studies would need to address these limitations in order to provide a wider and holistic picture of the association between breastfeeding duration and preschoolers' eating behaviors in low-income Latino populations living in their country of origin.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Beyond weight, eating behaviors may be also associated with breastfeeding. A considerable number of studies have revealed that breastfeeding is also associated with practices and interactions of individuals during food consumption in the early years (Borkhoff et al, 2018;Brown & Lee, 2015;Hathcock et al, 2014;Li et al, 2014;Mallan, Nambiar, et al, 2014) across different cultural contexts and geographical regions (Abou-ElWafa & El-Gilany, 2019; Caleyachetty et al, 2013;Muchacha & Mtetwa, 2014). Likewise, a study with Chilean Latino adolescents showed that shorter breastfeeding duration decreased the presence of satiety responsiveness and increased the risk of suffering overweight (Reyes et al, 2014).…”
Section: Association Among Eating Behaviors Bmi and Breastfeedingmentioning
confidence: 99%
“…[ 4 ] Childhood malnutrition is due, directly or indirectly, to mothers’ poor nutritional knowledge or lack thereof. [ 5 , 6 ] The Holy Quaran states that mothers should breastfeed their children for two full years. [ 7 ] According to the Millennium Development Goals (MDG), mothers’ training is a key factor in eliminating malnutrition among children younger than fi ve years of age.…”
Section: Introductionmentioning
confidence: 99%